As relações entre criança e natureza: o brincar vivo - Silva, Beatriz Rodrigues da (Universidade Federal de São Carlos, 2024)
The present thesis aims to understand and highlight experiences where play and nature contribute to the construction of children's knowledge through written works. This qualitative study focuses on building the State of Knowledge, utilizing bibliographic research to explore works produced on the subject between 2018 and 2023 in public universities in the state of São Paulo. Supported by a theoretical framework involving themes such as play, nature, and the teacher's role, an analysis was conducted on children's experiences with nature in early childhood education based on the selected works. Despite the scarcity of studies on this topic, it was possible to comprehend that free play in nature offers numerous experiences rich in discoveries and sensations for childhood. The importance of the teacher/adult's role was also evident, reflecting on their practices and seeking spaces and moments for children to play in nature.
The relationships between child and nature: the alive play
Keywords: Criança; Natureza; Brincar Livre; Educação Infantil; Child; Nature; Free Play; Early Childhood Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO